The Use of Methanolic Extract of Annona Muricata Linn Leaves as an Effective Anti-Hyperglycemia on Mice - Anak Agung Wiradewi Lestari (Journal of Global Pharma Technology, 2019)
Background: Extracts from various morphological parts of soursop leaf (Annona muricata Linn/Annonaceae) are widely used in many parts of the world for the management, control, and treatment of a human diseases, including diabetes mellitus (DM). This study investigates possible anti-hyperglycemia effects of methanolic extract of Annona muricata Linn in mice experimental paradigms of DM.Materials and Methods: The mice used were divided into three experimental groups. Group A served as ‘control’ animals and received sodium citrate buffer solution in quantities equivalent to the administered volumes of methanolic extract of Annona muricata Linn. Diabetes mellitus was induced in Groups B and C by intraperitoneal injections of streptozotocin (STZ, 80 mg/kg body weight). Group C were additionally treated with methanolic extract of Annona muricata Linn (100 mg/kg body weight, PO) for two weeks.Results: A statistically significant lower blood glucose level was found in Group C compared to Group B in sixth (215.14±78.37 vs 319.57±135.92 mg/dL) and seventh week (158.57±24.23 vs 238.85±51.35 mg/dL) of observation.Conclusion: Daily dose of 100 mg/kg body weight methanolic extract of Annona muricata Linn administration lowers blood glucose compared to those who did not receive in mice.